Purposiveness and Uniformity: the Problem of the Empirical Regularities in the Context of Kantian Transcendental Idealism - Jáuregui, Claudia (Estudios de Filosofía, 2013)
The principle of purposiveness that Kant introduces in the Kritik der Urteilskraft expresses the assumption that nature observes a uniformity suitable to our power of judgment. Since the principle is only regulative, it cannot, however, ensure this uniformity. The possibility of an empirical chaos remains open. But the existence of empirical regularities is required for the formation of empirical concepts, for the formulation of empirical laws, and for the possibility of empirical knowledge in general. It could be thought, in consequence, that they are a sort of “material” condition of possibility of experience, of which transcendental idealism cannot account. In this paper, we try to demonstrate that this is not the case. Empirical regularities are not conditions of the objectivity of experience, but they indeed collaborate with the progress of knowledge and with the possibility of its systematic organization.